2017
DOI: 10.1111/bph.13817
|View full text |Cite
|
Sign up to set email alerts
|

Dietary salt blunts vasodilation by stimulating epithelial sodium channels in endothelial cells from salt‐sensitive Dahl rats

Abstract: This article is part of a themed section on Spotlight on Small Molecules in Cardiovascular Diseases. To view the other articles in this section visit http://onlinelibrary.wiley.com/doi/10.1111/bph.v175.8/issuetoc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
47
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(56 citation statements)
references
References 55 publications
(73 reference statements)
8
47
1
Order By: Relevance
“…| 5 of 12 single cultured endothelial cells 7 was observed only under the unusual condition of elevated extracellular [Na + ] combined with elevated aldosterone (0.45 mmol/L). 19 More recent data with benzamil application showed no effect on baseline NO formation in line with the present observations but inhibited acetyl-choline-induced NO release in stark WT mice with eNOS inhibition (L-NAME infusion, 30 mg/kg/day for three days) (n = 9), three doses (5, 50, 500 μg/kg) of amiloride were administered intravenously at 10-minute interval, starting with an initial vehicle bolus injection. Ten minutes after the last dose, blood was collected from the arterial line.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…| 5 of 12 single cultured endothelial cells 7 was observed only under the unusual condition of elevated extracellular [Na + ] combined with elevated aldosterone (0.45 mmol/L). 19 More recent data with benzamil application showed no effect on baseline NO formation in line with the present observations but inhibited acetyl-choline-induced NO release in stark WT mice with eNOS inhibition (L-NAME infusion, 30 mg/kg/day for three days) (n = 9), three doses (5, 50, 500 μg/kg) of amiloride were administered intravenously at 10-minute interval, starting with an initial vehicle bolus injection. Ten minutes after the last dose, blood was collected from the arterial line.…”
Section: Discussionsupporting
confidence: 92%
“…In humans, only renal arteries exhibited faintly α and β ENaC products while no subunits were expressed in mammary arteries and cultured endothelial cells with highly significant amplification of endothelial markers. Previous data showed αβγENaC protein and mRNA in rodent cultured vascular smooth muscle cells 36 and endothelial cells 19 although others have reported absence of detectable αβγENaC from arterioles of the rat. 37 Likewise, αENaC transcripts are present in cultured human endothelial cells 2,3 but the current study could not reproduce this in human aortic endothelial cells.…”
Section: Discussionmentioning
confidence: 90%
“…Our recent studies demonstrated that elevated ENaC activity accounts for the reduced EDR by decreasing NO levels in endothelial cells from salt‐sensitive rats fed a high‐salt (HS) diet, and that blockade of ENaC by amiloride increased both phosphorylated eNOS and NO and, therefore, prevented the HS diet‐induced loss of vasorelaxation and endothelial dysfunction (Wang et al ). Others have also shown that inhibition of ENaC increases NOS phosphorylation and NO production in small‐diameter rat mesenteric arteries (Perez et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…The epithelial sodium channels (ENaC) play important parts in the regulation of total body Na + homeostasis and salt-sensitive hypertension (Peng et al, 2017;Wang et al, 2018). It is assembled from homologous gene products, mainly encoding α, β, and γ subunits (Canessa et al, 1994).…”
Section: Introductionmentioning
confidence: 99%